12b-hydroxy-des-D-garcigerin A enhances glucose metabolism in insulin-resistant HepG2 cells via the IRS-1/PI3-K/Akt cell signaling pathway. Issue 11 (1st November 2016) - Chen, Yu; Wang, Sha; Tian, Shi-Ting; Hu, Xin; Xu, Jing; Yang, Guang-Zhong; Wang, Chao-Yuan
Abstract: HepG2 cells were induced with a high concentration of insulin to establish an insulin-resistant cell model (HepG2/IR). The effect of 12b-hydroxy-des-D-garcigerin A (DGA) on the glucose consumption (GC) of HepG2/IR cells was analyzed with the glucose oxidase/peroxidase assay. The results showed that DGA significantly stimulated GC by enhancing the activity of hexokinase (HK) and pyruvate kinase (PK) in HepG2/IR cells. The cell signaling pathway by which DGA enhances the GC of HepG2/IR cells was explored. The results showed that DGA promoted the expression of insulin receptor (InsR) protein, and stimulated the expression of insulin receptor substrate 1 (IRS-1), phosphatidylinositol-3 kinase (p-PI3-K), and phospho-protein kinase B Serine 473 (p-AKT ser 473 ). Therefore, we concluded that DGA improved the insulin-resistance of HepG2/IR cells by inducing the IRS-1/PI3-K/Akt cell signaling pathway. Interestingly, DGA had no effect on the phosphorylation of threonine 172 (Thr 172 ) in AMP-activated protein kinase (AMPK).